Aspek Sentuhan Dalam Terapi Kelompok Terapeutik Untuk Meningkatkan Rasa Percaya Pada Bayi Usia 12-18 Bulan: Case Report - Safra Ria Kurniati; Zakiah Rahman (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2020)
Infancy is period of early life which basic abilities will determine success in the next phase. In this phase, the aspect of psychosocial development that must be achieved is to have a sense of trust, both for oneself, other people and the world around them. This study aims to find out how the application of therapeutic group therapy in increasing trust in infants and focus on aspects of touch. The method used is the case study. The results of this study indicate that the strengthening of touch in Therapeutic Group Therapy is able to foster and increase trust in infants in accordance with their psychosocial development tasks. Nurses as therapists need to emphasize this by encouraging mothers to not only give praise when the baby is successfully carrying out the task being trained, but also accompanied by physical affection sign such as touching, stroking, kissing and hugging the baby.Keywords: Infant, Touch, Therapeutic Group Therapy